Plant Rhizodeposition and Role in Sustainable Agriculture - Prasanthi , K.; Anitha , S. (Research Advances and Challenges in Agricultural Sciences Vol. 4, 2024)
Plants exude a large proportion of their photosynthetically assimilated carbon from their roots to soil. These root-released organic carbon compounds can significantly influence the chemical, physical and biological processes in the rhizosphere. Rhizodeposition is defined as all material lost from plant roots, including water-soluble exudates, secretions of insoluble materials, lysates, dead fine roots, and gases, such as CO2 and ethylene [1]. The high molecular weight rhizodeposits (e.g. mucilage, cellulose) which are not easily used by microorganisms make up the majority of carbon released from the root. However, the low molecular compounds (e.g. root exudates) are more diverse and have lot of potential functions. Root exudate compounds can be categorized into organic acids, amino acids, proteins, sugar, phenolics and other secondary metabolites which are more easily used by microorganisms. Root secretes mucilage, a viscous insoluble polysaccharide-rich substance, which aids in lubricating and protecting the root. Root volatile organic carbons have role in below ground plant interactions. The border cells released from root cap act as root extracellular traps for root pathogens. Plants have passive and active transports mechanisms to secrete these rhizodeposits into the rhizosphere. Root exudation pattern can be affected quantitatively and qualitatively by different physical, chemical, and biological factors. The amount of root exudates varies with plant species, the cultivar, and age of plants, soil properties, and stress factors. Rhizodeposits play an important role in soil and plant health by triggering various rhizosphere processes like nutrient solubilization, signaling for symbionts and pathogens, metal detoxification, promotion of soil aggregation, building of microbial communities and soil organic matter turn over etc., Hence, next-generation field management requires the promotion of microbial biomass formation through plant rhizodeposition to maintain healthy soils, ecosystem and climate.